A qualitative study exploring the support needs of newly qualified nurses and their experiences of an online peer support intervention. Issue 4 (4th July 2022) - Smythe, Analisa; Jenkins, Catharine; Bicknell, Sarah; Bentham, Peter; Oyebode, Jan
Abstract : Background: In the transitional period following registration, newly qualified nurses may feel socially isolated and easily overwhelmed by increases in accountability, workplace pressures and the psychological demands of the role. Such experiences place them at risk of burnout and leaving the profession. Aims: To explore newly qualified nurses' support needs and their experiences of an online peer support intervention. Method: Eighteen newly qualified nurses participated in online peer support groups. After 3 months participants took part in interviews exploring their support needs and experiences of the groups. Eight one-to one interviews were conducted between October 2019 and January 2020. Qualitative thematic analysis was used. Findings: Two themes identified were; "The Support needs of newly qualified nurses" with two subthemes, "The role of the newly qualified nurse" and "Unmet support needs"; "The online experience" with three subthemes, "Barriers to participation", "Anticipated benefits" and "Unmet expectations". Conclusion: Our findings suggested that there is insufficient support for newly qualified nurses. The newly qualified nurses wanted to use online support to help manage their stress. However, the organisation of online peer support needs careful consideration to ensure participation can be beneficial. Impact Statement: Online support requires careful design and clear support from employing organisations to promote improved transition experiences. Further research should focus on evaluating adjusted online support interventions.